FROM CONSENSUS TO SKEPTICISM? : ATTITUDES OF POLISH SOCIETY TOWARDS EUROPEAN INTEGRATION - SZCZEPANKIEWICZ-RUDZKA, Ewa (Studia Universitatis Babes-Bolyai Studia Europaea, 2018)
Public opinion surveys conducted in Poland systematically since 2001 confirmed a high, more than 80-per cent, support for our membership in the EU structures. While the need for Poland's membership in the European Union has never been questioned, the issue of the development of European integration has aroused controversy and is still a cause of dispute. The hypothesis of the paper bases on two statements: (1) Polish society attitude towards European integration is more skeptical than would be apparent from the data on general support for EU membership, (2.) Current government, which has established Euroscepticism as the main direction of its foreign policy does not diverge from the mood and social expectations.